2020
DOI: 10.1007/978-3-030-58147-3_3
|View full text |Cite
|
Sign up to set email alerts
|

User-Defined Mid-Air Haptic Sensations for Interacting with an AR Menu Environment

Abstract: Interfaces that allow users to interact with a computing system by using free-hand mid-air gestures are becoming increasingly prevalent. A typical shortcoming of such gesture-based interfaces, however, is their lack of a haptic component. One technology with the potential to address this issue, is ultrasound mid-air haptic feedback. At the moment, haptic sensations are typically designed by system engineers and experts. In the case of gestural interfaces, researchers started involving non-expert users to defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
(14 reference statements)
0
6
0
Order By: Relevance
“…We examined associative descriptions, using a think-aloud method based on a set of easily recognizable and distinguishable forms whose selection process we described in detail. A more top-down approach has been followed by Van den Bogaert and Geerts ( 2020 ) as well as Wobbrock et al ( 2009 ). They used a so-called “end-user elicitation study” to examine affordances of gesture-specific mid-air-haptic feedback and gestures for surface computing.…”
Section: Discussionmentioning
confidence: 99%
“…We examined associative descriptions, using a think-aloud method based on a set of easily recognizable and distinguishable forms whose selection process we described in detail. A more top-down approach has been followed by Van den Bogaert and Geerts ( 2020 ) as well as Wobbrock et al ( 2009 ). They used a so-called “end-user elicitation study” to examine affordances of gesture-specific mid-air-haptic feedback and gestures for surface computing.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these cues are purely abstract (e.g. [15,6]), others are designed to be evocative of underlying virtual mechanism (e.g. mid air buttons [37]).…”
Section: Umh Renderingmentioning
confidence: 99%
“…Dzidek et al [15] design and evaluate a set of abstract UMH stimuli to support a wide range of interactions in an AR demonstrator. Van den Bogaert et al [6] present a study on the selection of abstract UMH patterns intended for providing users with feedback when interacting with menus in mid-air in AR. Their study demonstrate a notable preference for relatively simple stimulus design when the aim is to support interaction, with a strong focus on the use of stimulus intensity and temporal parameters (continuous vs. discrete) as rendering parameters.…”
Section: Umh Renderingmentioning
confidence: 99%
“…e fourth most popular interaction technique was pinch, used for both scrolling [3,7] and drag and drop [27] tasks, which are key interactions for more advanced applications. Farhadi-Niaki et al [27] showed that the pinch gesture demonstrated better performance than hand circling for a drag and drop task in a WIMP interface.…”
Section: Interaction Techniques Suitable For Translation Taskmentioning
confidence: 99%
“…Midair gestural interaction applications have been gaining popularity for large public displays [1,2] and augmented reality [3] and in smart spaces [4]. One of the most frequently used actions in midair interaction with large screens is the one that translates (drags or moves) objects (or cursor) to an indicated target position while retaining their object's size and rotation [5,6].…”
Section: Introductionmentioning
confidence: 99%